The Coming Of Paper - Innis, Harold (Intermédialités / Intermediality, 2011)
During the last dozen years of his life, Harold A. Innis assembled a massive set of writings entitled A History of Communications. The excerpt published here is from the first section of Chapter IV, “The Coming of Paper,” which begins with the production of paper in China “as early as 105 A.D.” and concludes with the westward diffusion of paper-making during the Middle Ages. While the manufacture of paper and its spread is at the centre of Innis’s discussion, he gives considerable attention to the related technologies of ink production, block printing, and the introduction of movable type. He also traces the onset of paper and printing within a number of different socio-cultural contexts, including China, India, Korea, the Muslim world, and Europe. After detailing how the paper-manufacturing process gained a foothold in Europe—becoming a formidable rival to parchment—Innis examines how paper was linked to the broader process of key developments such as the extension of credit, the revival of antiquity, the reformation of the Church, and the rise of the modern state.